'Opening the gate' – What's the difference?. Issue 2 (1st September 2011) - Groves, Karen; Baldry, Catherine
Abstract : Background: NICE Supportive and Palliative Care Improving Outcomes Guidance 2004 states clearly that health professionals should be in a position to assess the spiritual and religious needs of patients and either meet these needs or facilitate others to do so. A cancer network audit in 2006 showed that staff felt quite unprepared for this role. Aim: To see if a one day interactive course to raise awareness of spiritual and religious needs was effective in increasing staff confidence in this area of support. Method: A spiritual support education programme was developed, which could be rolled out across the cancer network. The course was then offered to participants who chose to attend. Each participant was asked to complete a pre and post course questionnaire and course evaluation. Results: 159 participants attended the first 12 courses. 156 completed pre and post course questionnaires and 104 completed pre and post course confidence visual analogue scales which were compared. Many of the items suggest improvement from before the course to immediately afterwards, for example, pre course only 6% participants felt that they understood the nature of spiritual assessment 'very well', 36% 'quite well', 57% 'a little' or 'not at all'. After the course 57% participants scored the answer as 'very well', and 40% 'quite well' with only 3% 'a little'. Pre course the mean visual analogue score for confidence in assessing spiritual needs was 4.00 and afterwards 6.76 (where 0 was no confidence) and for assessing religious needs pre course 4.71 and post course 7.07. Conclusion: It appears that this course was successful in raising awareness and understanding of the nature of spiritual assessment and raises the confidence of participants in assessing spirituals needs. It remains to be seen whether the improvement is maintained once the participants return to the workplace.